IMPLEMENTASI APLIKASI CALISTUNG DENGAN PENDEKATAN MULTIMEDIA DEVELOPMENT LIFE CYCLE PADA PLATFROM ANDROID - Muhammad Arief Wardana; Taqrim Ibadi (Infotech: Journal of Technology Information, 2025)
Android-based learning media is an essential tool in supporting the learning process, especially for elementary school students. One of the main problems in learning at this level is the lack of visualization during the delivery of learning materials, which often results in decreased interest and increased boredom among students. The use of “calistung” (reading, writing, and arithmetic) learning media can help make the learning process more engaging and interactive. This media is equipped with features such as images, text, audio, and animations that enhance students’ interest and facilitate a better understanding of the subject matter. In addition, it can reduce boredom during teaching and learning activities. The development of this Android-based calistung learning media utilizes the MDLC (Multimedia Development Life Cycle) approach, which has proven to be effective. This method allows students to continue learning without feeling bored until they fully understand the material. Overall, the implementation of Android-based calistung learning media provides significant benefits for elementary school students. It is expected to become an alternative learning option that makes the learning experience more interactive and enjoyable.